Investigating the effects of age, IQ, dosing, and anthropometric measures on the treatment persistence in long-term methylphenidate use. (2nd May 2023) - Tuncturk, Mustafa; Ermis, Cagatay; Buyuktaskin, Dicle; Halac, Eren; Sut, Ekin; Ozkan, Oben; Gundogan, Nazan; Unutmaz, Guldal; Ciray, R. Ogulcan; Turan, Serkan; Pekcanlar, Aynur Akay
Abstract: Objectives: This study aimed to determine anthropometric and clinical correlates of persistence to methylphenidate (MPH) treatment in Turkish youth with attention-deficit hyperactivity disorder (ADHD). Methods: Data from medical records of 518 children and adolescents with ADHD were recorded between March 2012 and January 2022. Clinical variables of patients persistent to MPH ≥ 2 years were compared with those of the non-persistent group. Children and adolescent age groups were compared using Kaplan–Meier estimates for treatment drop-outs. Cox regression analysis until the treatment drop-out was implemented to calculate hazard ratios (HRs) for gender, age, full-scale IQ, and anthropometric measures. Weight, height, and body mass index (BMI) z-scores were calculated per national guidelines. Results: Persistent and non-persistent study groups had similar full-scale IQ, weight, height, and BMI z-scores at treatment onset. The mean MPH dose was significantly higher in the persistent group compared to the non-persistent counterparts (31.43 ± 10.70 vs. 24.28 ± 9.60 mg/d, p < 0.001, d = 0.70). Compared to children, the adolescents showed earlier treatment drop-outs in males ( p < 0.001) but not in females ( p = 0.110). Younger age showed a positive effect on treatment persistence. Conversely, baseline BMI and IQ scores were not associated with long-term persistence. Discussion: Our study demonstrated lower daily doses and older age-onset were associated with early drop-outs in MPH treatment. These findings supported the notion that effective dosing strategies at younger ages could increase the sustainability of the treatment with MPH in the Turkish population.